Relevance of force-velocity and change of direction assessments for the ranking position in elite junior tennis players - Reiner Volk, N.; Vuong, J.-L.; Ferrauti, A. (Frontiers in Sports and Active Living, 2023)
Purpose: This study aimed to correlate sprint mechanical parameters (SMP) of a linear sprint (LS) and a tennis specific modified 505 (Tm505) change of direction (CoD) test obtained with a motorized resistance device (MRD) to the current tennis ranking position (RP).